Effects of oseltamivir treatment of index patients with influenza on secondary household illness in an urban setting in Bangladesh: secondary analysis of a randomised, placebo-controlled trial. Issue 6 (June 2015) - Fry, Alicia M; Goswami, Doli; Nahar, Kamrun; Sharmin, Amina T; Rahman, Mustafizur; Gubareva, Larisa; Trujillo, Alma; Barnes, John; Azim, Tasnim; Bresee, Joseph; Luby, Stephen P; Brooks, W Abdullah
Summary Background Antiviral drugs are a proposed medical intervention to reduce household transmission of influenza viruses. In a previously described randomised, placebo-controlled trial in Dhaka, Bangladesh, we showed that oseltamivir treatment of index patients was able to reduce influenza symptom duration and virus shedding. In a further analysis that is part of the same study, we aimed to assess efficacy of oseltamivir to reduce secondary household illnesses in the same cohort. Methods In this double-blind oseltamivir efficacy trial, we identified index patients aged older than 1 year through surveillance of households in Dhaka, Bangladesh. We randomly allocated eligible patients (1:1) to receive oseltamivir or placebo twice-daily for 5 days, and we stratified them by enrolment 48 h versus 48–120 h since illness onset. Participants provided nasal wash specimens at enrolment and 2, 4, and 7 days after enrolment and were visited daily by a research assistant to record symptoms, both in index patients and in household members. For this part of the study, household members were asked to give respiratory specimens for influenza PCR testing. Our primary outcomes were household secondary illness and PCR-confirmed influenza virus infection, assessed in household members of all randomly allocated index patients. This trial is registered with ClinicalTrials.gov, number NCT00707941. Findings From May 11, 2008, to Dec 31, 2010, we enrolled 1190 index patients with 4694 household members. 592 patients were allocated to placebo (2292 household members) and 598 to oseltamivir (2402 household members). Household secondary illness was lower in the oseltamivir group (196 [8%] influenza cases) than in the placebo group (233 [10%]; odds ratio [OR] 0·77, 95% CI 0·60–0·98, p=0·031). PCR-confirmed influenza virus infection did not differ between the placebo (103 [5%]) and oseltamivir groups (92 [4%]; 0·84, 0·59–1·19, p=0·319); however, only 243 (57%) of ill household members gave a specimen for analysis. Interpretation In a crowded, low income setting, oseltamivir treatment of index patients resulted in a small reduction of secondary influenza in their households. Even this slight reduction, in the setting of widespread antiviral use during a community influenza outbreak, might result in reductions in overall disease burden. Funding Centers for Disease Control and Prevention (in an agreement with the International Centre for Diarrhoeal Disease Research, Bangladesh).